2004
DOI: 10.1089/1530366041210747
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Relatedness of Deer Mice (Peromyscus maniculatus) Infected with Sin Nombre Virus

Abstract: The deer mouse (Peromyscus maniculatus) is the primary rodent host of Sin Nombre virus (SNV), the principal etiologic agent of hantavirus pulmonary syndrome in the United States. Many characteristics of SNV infections of deer mice are unknown. To better understand the transmission mechanisms of SNV in deer mice, we conducted mark-recapture sampling and genetic analyses to study deer mouse population density and genetic relatedness from 2001 to 2002. We genotyped each deer mouse at 10 microsatellite loci to est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…In nature, the transmission of Old and New World hantaviruses between rodent reservoirs or to a nonreservoir rodent is thought to be primarily through aggressive behavior and exposure to saliva and excreta (121,143,369). Infection in the rodent has been thought to be subclinical.…”
Section: Rodent Reservoirs Of Old World Hantavirusesmentioning
confidence: 99%
“…In nature, the transmission of Old and New World hantaviruses between rodent reservoirs or to a nonreservoir rodent is thought to be primarily through aggressive behavior and exposure to saliva and excreta (121,143,369). Infection in the rodent has been thought to be subclinical.…”
Section: Rodent Reservoirs Of Old World Hantavirusesmentioning
confidence: 99%
“…In the wild, immunosuppression, stresses, or seasonal signals are likely to induce an increase in hantavirus replication, shedding, and consequently transmission. Moreover, bite wounds might be more productive routes of transmission than inhalation (62)(63)(64)(65)(66)(67). Urine aerosols generated during aggression behavior could also explain the correlation between wounding and hantavirus infection in natural reservoirs.…”
Section: Reservoir Hosts Virus Evolution and Transmissionmentioning
confidence: 99%
“…Depending on the population density, up to 50% of any given population of rodents are seropostive and considered as silent carriers for hantaviruses. Through experimental infections and field surveys, it has been shown that the transmission among rodents is exclusively horizontal and it occurs via inhalation of infected aerosols, through saliva or excreta, biting, and other aggressive behavioral interactions Glass et al, 1988;Hinson et al, 2004;Hutchinson et al, 2000;Kariwa et al, 1998;Lee et al, 1981a,b;Root et al, 2004). Unlike other rodent-borne viruses such as arenaviruses, there is no vertical transmission from the dam to its offspring, and maternal antibodies can protect offspring from infection for several months (Kallio et al, 2006;Taruishi et al, 2008).…”
Section: B Reservoir Hosts Of Hantavirusesmentioning
confidence: 99%